A new tyrannosaurid (Dinosauria: Theropoda) from the Upper Cretaceous Menefee Formation of New Mexico - McDonald, Andrew T. (PeerJ, 2018)
The giant tyrannosaurids were the apex predators of western North America and Asia during the close of the Cretaceous Period. Although many tyrannosaurid species are known from numerous skeletons representing multiple growth stages, the early evolution of Tyrannosauridae remains poorly known, with the well-known species temporally restricted to the middle Campanian-latest Maastrichtian (∼77–66 Ma). The recent discovery of a new tyrannosaurid, Lythronax argestes, from the Wahweap Formation of Utah provided new data on early Campanian (∼80 Ma) tyrannosaurids. Nevertheless, the early evolution of Tyrannosauridae is still largely unsampled. We report a new tyrannosaurid represented by an associated skeleton from the lower Campanian Allison Member of the Menefee Formation of New Mexico. Despite fragmentation of much of the axial and appendicular skeleton prior to discovery, the frontals, a metacarpal, and two pedal phalanges are well-preserved. The frontals exhibit an unambiguous autapomorphy and a second potential autapomorphy that distinguish this specimen from all other tyrannosaurids. Therefore, the specimen is made the holotype of the new genus and species Dynamoterror dynastes. A phylogenetic analysis places Dynamoterror dynastes in the tyrannosaurid subclade Tyrannosaurinae. Laser-scanning the frontals and creation of a composite 3-D digital model allows the frontal region of the skull roof of Dynamoterror to be reconstructed.